Prevalence of Borrelia burgdorferi sensu lato in Ixodes ricinus ticks and assessment of entomological risk index at localities in Belgrade - Krstić, Milena; Stajković, Novica; Lazić, Srđan (Vojnosanitetski pregled, 2017)
Background/Aim. The first case of human Lyme borreliosis (LB) in Serbia was recorded in 1987. The number of reported LB cases has increased in the past decade. The aim of this study was to estimate the density of Ixodes ricinus (I. ricinus) ticks, the prevalence of Borrelia burgdorferi sensu lato (B. burgdorferi) in them, and entomological risk index (ERI) at 19 Belgrade localities which were grouped into three categories (forests, park-forests, parks). The values of ERI were compared with the number of tick bites in humans. Methods. Ticks were collected monthly by using the flag hours method and the infection rate was determined by using dark field microscopy. The ERI value was calculated for each locality where the ticks were collected. The related data about tick bites was obtained from the patient protocol of the Institute of Epidemiology, Military Medical Academy, Belgrade. Results. The total number of collected ticks, the number of nymphs and the infection rates of the nymphs were significantly higher in forests (p < 0.05) than park-forests and parks. Statistically, the ERI value was significantly higher in forests than parks of Belgrade (χ2 = 7.78, p < 0.01). In March and July, the ERI value was also significantly higher in forests, than park-forests (p < 0.01) and parks (p < 0.01). May was the month with the highest ERI value in each ecological category (forests p < 0.05; park-forests p < 0.01; parks p < 0.001). However, the number of tick bites in humans did not correlate with ERI values. Conclusion. The obtained results indicate that the risk of tick bite and human exposure to B. burgdorferi sensu lato is present at all selected localities in Belgrade. For a more comprehensive Lyme disease risk assessment the method of entomological risk index assessment should be combined with other methods, taking into consideration all tick stages and the behaviour and habits of people who may get infected B. burgdorferi sensu lato.